The myonuclear DNA methylome in response to an acute hypertrophic stimulus. Issue 11 (1st November 2020) - Von Walden, Ferdinand; Rea, Matthew; Mobley, C. Brooks; Fondufe-Mittendorf, Yvonne; McCarthy, John J.; Peterson, Charlotte A.; Murach, Kevin A.
ABSTRACT: In addition to multi-nucleated muscle fibres, numerous resident and infiltrating mononuclear cells populate the muscle compartment. As most epigenetic assays in skeletal muscle are conducted on whole tissue homogenates, essentially nothing is known about regulatory processes exclusively within muscle fibres in vivo . Utilizing a novel genetically modified mouse model developed by our laboratory, we (1) outline a simple and rapid workflow for isolating pure myonuclei from small tissue samples via fluorescent activated cell sorting and extracting high-quality large-fragment DNA for downstream analyses, and (2) provide information on myonuclear and interstitial cell nuclear CpG DNA methylation via reduced representation bisulphite sequencing (RRBS) using mice that were subjected to an acute mechanical overload of the plantaris muscle. In 3-month-old mice, myonuclei are 50% of total nuclei in sham and 30% in 3-d overloaded muscle, the difference being attributable to mononuclear cell infiltration and proliferation with overload. In purified myonuclei, pathway analysis of hypomethylated promoter regions following overload was distinct from interstitial nuclei and revealed marked regulation of factors that converge on the master regulator of muscle growth mTOR, and on autophagy. Specifically, acute hypomethylation of Rheb, Rictor, Hdac1, and Hdac2, in addition to a major driver of ribosome biogenesis Myc, reveals the epigenetic regulation of hypertrophic signalling within muscle fibres that may underpin the long-term growth response to loading. This study provides foundational information on global myonuclear epigenetics in vivo using RRBS, and demonstrates the importance of isolating specific nuclear populations to study the epigenetic regulation of skeletal muscle fibre adaptation.